Seed rain in two areas with different relief types in a tropical rainforest (Research, Society and Development, 2022)
Seed rain participates in species enrichment during the natural regeneration of terrestrial ecosystems, as this ecological process promotes gene flow and the maintenance of forest biodiversity. However, few studies assessed variations in seed rain related to environmental heterogeneity inside forests. We studied the influence of relief (flat or slope areas) on the seasonal and monthly variation in density, floristic composition, and richness of the seed rain in an urban fragment of Atlantic Forest. We carried out the present study in Rain Tropical Forest, Northeastern Brazil. We selected two areas within the fragment: one with flat relief and the other on a slope. In each relief type we set up 20 0.25-m2 seed collectors, in a total of 40 units, to quantify seed rain. After ten months of study, we counted 9,474 seeds: 8,061 in the flat area and 1,413 in the slope area. There were significant differences in dispersal syndromes and plants habit between relief types. The seed density in the flat area differed between seasons and the species richness varied seasonally in both areas. There were variations in floristic composition between seasons in the flat and slope areas. Seed density was higher in December and January in the flat area. Differences in seed rain suggest that it is influenced by spatial heterogeneity and climate seasonality, and that the areas with different kinds of relief are important for the biodiversity conservation.